Fear avoidance beliefs and quality of life quality after lumbar disc surgery - Dogan Gucluhan Guclu; Omer Senormanci; Oya Gonullu; Musa Cirak; Guliz Senomanci; Furuzan Kokturk (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Fear avoidance beliefs (FAB) in low back pain (LBP) are associated with disability and pain. There is no data on how changes in FAB affect disability and other factors after lumbar disc surgery. The aim of this study was to evaluate the effects of lumbar disc surgery on FAB and to investigate whether FAB changes predict changes in emotions, disability, and quality of life after lumbar disc surgery. 106 patients with chronic LBP were evaluated 1 day preoperatively and 3 months postoperatively. Sociodemographic questionnaire, Visual Analog Scale (VAS), Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), Fear and Avoidance Beliefs Qquestionnaire (FABQ), Oswestry Disability Index (ODI), and Short form-36 (SF-36) Health Survey Questionnaire were used. The end point ODI, VAS, BDI, BAI, FABQ fear avoidance (work) scores, most of SF-36 the subscale scores were significantly lower than the baseline scores. According to correlation analyses between mean changes in the outcome measures, there was no significant relationship between changes in fear avoidance (physical), fear avoidance (work) and other outcome measures. In conclusion, future research is needed to evaluate the effect of lumbar disc surgery on FAB. [JCBPR 2017; 6(1.000): 1-8]